Analisis Sistem Manajemen Persediaan Dengan Metode Economic Order Quantity (EOQ) - Muhammad Habibie Satria; Sinta Dewi (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Inventory is crucial and very important in every production series. So good inventory management is needed to increase the optimization of production activities. Decision making in order to reduce risks in the warehouse if procurement of too many goods in a short period results in increased storage costs. This research proposes inventory management using the Economic Order Quantity method with the results for grinding blades, bolts and acetylene respectively being EOQ of 136.7; 154.9; and 42.42.